Different clamp stress impact on losses and flux distribution between two of 3 phase distribution transformer 1000 kVA assembled with stagger yoke of transformer core lamination - Ismail, Daut, Prof. Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://www.ieee.org/